Brain abnormalities and neurodevelopmental delay in congenital heart disease: systematic review and meta‐analysis. (10th December 2013) - Khalil, A.; Suff, N.; Thilaganathan, B.; Hurrell, A.; Cooper, D.; Carvalho, J. S.
ABSTRACT Objectives Studies have demonstrated an association between congenital heart disease (CHD) and neurodevelopmental delay. Neuroimaging studies have also demonstrated a high incidence of preoperative brain abnormalities. The aim of this study was to perform a systematic review to quantify the non‐surgical risk of brain abnormalities and of neurodevelopmental delay in infants with CHD. Methods MEDLINE, EMBASE and The Cochrane Library were searched electronically without language restrictions, utilizing combinations of the terms congenital heart, cardiac, neurologic, neurodevelopment, magnetic resonance imaging, ultrasound, neuroimaging, autopsy, preoperative and outcome. Reference lists of relevant articles and reviews were hand‐searched for additional reports. Cohort and case–control studies were included. Studies reporting neurodevelopmental outcomes and/or brain lesions on neuroimaging in infants with CHD before heart surgery were included. Cases of chromosomal or genetic abnormalities, case reports and editorials were excluded. Between‐study heterogeneity was assessed using the I2 test. Results The search yielded 9129 citations. Full text was retrieved for 119 and the following were included in the review: 13 studies (n = 425 cases) reporting on brain abnormalities either preoperatively or in those who did not undergo congenital cardiac surgery and nine (n = 512 cases) reporting preoperative data on neurodevelopmental assessment. The prevalence of brain lesions on neuroimaging was 34% (95% CI, 24–46; I2 = 0%) in transposition of the great arteries, 49% (95% CI, 25–72; I2 = 65%) in left‐sided heart lesions and 46% (95% CI, 40–52; I2 = 18.1%) in mixed/unspecified cardiac lesions, while the prevalence of neurodevelopmental delay was 42% (95% CI, 34–51; I2 = 68.9). Conclusions In the absence of chromosomal or genetic abnormalities, infants with CHD are at increased risk of brain lesions as revealed by neuroimaging and of neurodevelopmental delay. These findings are independent of the surgical risk, but it is unclear whether the time of onset is fetal or postnatal. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.